Reading characteristics of deaf and hard-of-hearing pupils - Karić Jasmina; Ristić Siniša; Medenica Snežana; Tadić Vaska; Slavnić Svetlana (Vojnosanitetski Pregled)
Background/Aim. Speech motor mechanisms play a crucial role in the process of demutization, due to the fact that they cover all the elements of the successive development of spech production movements leading to speech formation (socalled kinesthesia in speach). The aim of this study was to estimate the impact of perceptual motor actions on the cognitive process of reading in 130 students in regular schools and schools for the deaf and hard-of-hearing children in the Republic of Serbia. Methods. Kostić and Vladisavljević test consisted of the ten levels weight was used for the assessment of reading speed. To assess understanding of text read by verbal responses, we used three-dimensional adapted reading test of Helene Sax. Results. The triage-articulation test for assessing reading speed (Kostić and Vladisavljević’s test according to the weight of ten levels, revealed that students in regular schools statistically significantly faster read texts as compared to the deaf students. The results of the threedimensional adapted reading test of Helena Sax, show that the words learned by deaf children exist in isolation in their mind, ie, if there is no standard of acoustic performance for graphic image, in deaf child every word, printed or written, is just the sum of letters without meaning. Conclusion. There is a significant difference in text reading speed and its understanding among the children who hear and the deaf and hard of-hearing children. It is essential that in deaf and heard-of hearing children education, apart from the development of speech, parallelly use the concept of semantic processing in order to get each word by the fullness of its content and the possibility of expanding its meaning in a variety of assets.